Status Gizi Mahasiswa Sebelum dan Di Saat Pandemi COVID-19 - Bolang, Christy R.; Kawengian, Shirley E. S.; Mayulu, Nelly; Bolang, Alexander S. L. (Jurnal Biomedik : JBM, 2021)
Abstract: The COVID-19 pandemic has caused Public Health Emergencies as well as non-natural disasters. Therefore, it is necessary to do countermeasures including prevention and control. Management policies, can result in changes to a person's diet, sleep habits, physical activity, and nutritional status. The purpose of this study, is to know the differences between the nutritional status of student batch of 2019 Medical Education Study Program Faculty of Medicine Sam Ratulangi University, before and during the COVID-19 pandemic. This study is an observational retrospective study and the data were obtained through an e-questionnaire using the google form application. As a result, 112 samples were obtained through data before the pandemic with nutritional status; underweight 14.3%, normal 43.8%, overweight at risk 17.0%, obese I 19.6%, obese II 5.4%. While the nutritional status during the pandemic; underweight 17.0%, normal 48.2%, overweight at risk 17.9%, obese I 13.4%, obese II 3.6%. Statistical tests using the Wilcoxon Rank Test showed that the nutritional status category during the pandemic, was lower than the nutritional status category before the pandemic. (p <0.05). The result of this study concluded that there is a diminution in Nutritional Status category of Student Batch of 2019 Medical Education Study Program Faculty of Medicine Sam Ratulangi University during the COVID-19 pandemic.Keywords: Nutritional Status, COVID-19. Abstrak: Pandemi COVID-19 menimbulkan Kedaruratan Kesehatan Masyarakat serta bencana nonalam, sehingga perlu dilakukan upaya penanggulangan termasuk pencegahan dan pengendaliannya. Kebijakan-kebijakan penanganannya, seperti karantina, bisa mengakibatkan perubahan terhadap pola makan, kebiasaan tidur, aktivitas fisik, dan Status Gizi seseorang. Tujuan penelitian ini yaitu diketahuinya perbedaan antara status gizi mahasiswa Angkatan 2019 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi pada masa sebelum dan di saat pandemi COVID-19. Penelitian ini merupakan suatu observational retrospective study dan data diperoleh melalui e-questionnaire dengan aplikasi google form. Hasil penelitian terhadap 112 sampel, diperoleh data pada masa sebelum pandemi dengan status gizi; underweight 14,3%, normal 43,8%, overweight at risk 17,0%, obese I 19,6%, obese II 5,4%. Status gizi pada masa pandemi; underweight 17,0%, normal 48,2%, overweight at risk 17,9%, obese I 13,4%, obese II 3,6%. Uji statistik dengan Wilcoxon Rank Test diperoleh kategori status gizi pada masa pandemi lebih rendah dibandingkan dengan kategori status gizi sebelum masa pandemi (p < 0,05). Dan disimpulkan bahwa terdapat penurunan kategori Status Gizi pada Mahasiswa Angkatan 2019 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi pada masa pandemi COVID-19.Kata Kunci: Status Gizi, COVID-19